Legal Accountability of Government Administrative Officials for the Issuance of Dual Land Ownership Certificates (A Study on the Ownership Certificate of Mangli Community Health Center, Jember Regency) - Nazylatul Muawanah; Ahmad Suryono (Empat Sembilan Publisher, 2026)
The issuance of two land title certificates over the same parcel of land constitutes a serious problem in land administration and may undermine legal certainty in land registration. This study aims to analyze the form of administrative legal responsibility of land officials for the issuance of overlapping land certificates, particularly in the case of the Puskesmas Mangli property in Jember Regency. The research employs a normative juridical method with a statutory and conceptual approach by examining relevant laws and regulations concerning administrative governance and land administration. The results show that the issuance of two certificates occurred due to inadequate verification of physical and juridical data during the land registration process, particularly in the examination of land history and cadastral records. In administrative law, a land certificate is considered a state administrative decision that must fulfill the requirements of authority, procedure, and substance. If these requirements are not met, the decision may be declared invalid and subject to administrative correction. The study concludes that the administrative legal responsibility arising from the issuance of overlapping certificates is primarily a responsibility of office, as the certificate was issued by officials exercising their official authority. Such responsibility may be realized through administrative actions including cancellation, revocation, or correction of the defective certificate by the National Land Agency. This mechanism reflects the application of the principle that administrative authorities have the power to revoke their own decisions when administrative defects are identified. The findings highlight the importance of strengthening verification procedures and administrative supervision in land registration to ensure legal certainty and prevent similar disputes in the future.